Low-density lipoprotein receptor-related protein 1 regulates muscle fiber development in cooperation with related genes to affect meat quality. (15th April 2019) - Lv, Chao; Niu, Shuling; Yan, Shouqing; Bai, Chunyan; Yu, Xi; Hou, Jiani; Gao, Wenjing; Zhang, Jinyu; Zhao, Zhihui; Yang, Caini; Zhang, Yonghong
ABSTRACT: Low-density lipoprotein receptor-related protein 1 ( LRP1 ) is an important signal protein that is widely involved in physiological processes, such as lipid metabolism, cell movement, and disease processes. However, the relationship between LRP1 and meat quality remains unknown in chickens. The present study aimed to investigate the correlation between LRP1 and meat quality that builds on our preliminary research, as well as to reveal the underlying molecular mechanism of LRP1 on meat-quality traits. The results showed that LRP1 was significantly correlated with shear force ( P < 0.05). Several key genes involved in muscle growth and development, including IGF -1, IGFBP -5, IGF -1R, IGF -2, and MyoD, were down-regulated significantly ( P < 0.05 or P < 0.01), and MSTN was up-regulated significantly ( P < 0.01) in the presence of LRP1 interference. Cell proliferation- or apoptosis-related genes, including PMP 22, CDKN 2C, and p53, increased significantly ( P < 0.05 or P < 0.01), whereas Bcl-x decreased significantly ( P < 0.05) in the RNAi group. We conclude that LRP1 regulates muscle fiber development in cooperation with related genes that affect myoblast proliferation and apoptosis, thereby impacting shear force in chickens. This study will provide a valuable resource for biological investigations of muscle growth and meat-quality-related genes in chickens. The results could be useful in identifying candidate genes that could be used for selective breeding to improve meat quality.